THE INFLUENCE OF THE UNITED STATES AMBITION IN CONTROLLING OVER CASPIAN OIL TO THE PROLONGED POLITICAL DISPUTE BETWEEN ARMENIA AND AZERBAIJAN IN 1994-2005 - Wahyu Tri H (Universitas Muhammadiyah Yogyakarta, 2009)
THE INFLUENCE OF THE UNITED STATES AMBITION IN CONTROLLING OVER CASPIAN OIL TO THE PROLONGED POLITICAL DISPUTE BETWEEN ARMENIA AND AZERBAIJAN IN 1994-2005